Acceptability, motivation and the prospect of cure for people living with HIV and their healthcare providers in HIV cure-focused treatment interruption studies - Lau, Jillian S. Y.; Smith, Miranda Z.; Allan, Brent; Martinez, Cipriano; Power, Jennifer; Lewin, Sharon R.; McMahon, James H. (AIDS research and therapy, 2020)
Background Analytical treatment interruptions (ATI) are commonly used clinical endpoints to assess interventions aimed at curing HIV or achieving antiretroviral therapy (ART)-free HIV remission. Understanding the acceptability of ATI amongst people living with HIV (PLHIV) and their HIV healthcare providers (HHP) is limited. Methods Two online surveys for PLHIV and HHP assessed awareness and acceptability of ATI, and understanding of the prospect for HIV cure in the future. Responses were collected from July 2017–January 2018. A descriptive analysis was performed and similar questions across the two surveys were compared using χ squared test. Results 442 PLHIV and 144 HHP completed the survey. 105/400 (26%) PLHIV had ever interrupted ART, 8% of which were in a clinical trial. Altruistic motivations were drivers of participation of PLHIV in cure related research. 81/135 (60%) HHP would support their patients wishing to enrol in an HIV cure-focused trial, but fewer would promote and allow such participation (25% and 31% respectively). Compared to HHP, PLHIV were more likely to believe that an HIV cure would be achievable within 10 years (55% vs. 19%, p < 0.001), had less awareness of ATI (46% vs. 62%, p < 0.001) and were less likely to have had experience of either participation or enrolment in an ATI study (5% vs. 18%, p < 0.001) Conclusion PLHIV were more optimistic about the potential for HIV cure. HHP had more direct experience with HIV cure-focused studies. Educational strategies are required for both groups to increase understanding around ATIs in HIV cure research but should be tailored specifically to each group.